Severe respiratory illness of unexplained etiology during the 2009 influenza pandemic: Analysis of Clinical Features and Outcomes - Jennifer Potter; Salaheddin M. Mahmud (Human Vaccines & Immunotherapeutics, 2017)
During the 2009 H1N1 pandemic, 99 severe respiratory illness (SRI) cases were reported in Manitoba. The cause of illness was often not established. Many of these cases may have been unidentified pH1N1. We conducted a chart audit of all severe SRI cases and compared their demographic and clinical characteristics to severe pH1N1 cases. 73 of the 170 cases reviewed were confirmed pH1N1, 53 were SRI with an identified cause, and 44 were SRI with no identified cause. Unexplained SRI cases were similar to pH1N1 cases in terms of risk factors, geographic and temporal distribution, clinical presentation and outcomes. We found that unexplained SRI cases often resembled severe pH1N1 cases, suggesting that these cases were at least in part caused by undiagnosed pH1N1. The overall impact of the pandemic may have been underestimated, especially among the most severely affected indigenous and northern communities.